Arsenic Removal from Aqueous Solution Using Pure and Metal-Doped Titania Nanoparticles Coated on Glass Beads: Adsorption and Column Studies. (16th July 2013) - Danish, M. Ihsan; Qazi, Ishtiaq A.; Zeb, Akif; Habib, Amir; Awan, M. Ali; Khan, Zahiruddin
Abstract : Nanosized metal oxide, Titania, provides high surface area and specific affinity for the adsorption of heavy metals, including arsenic (As), which is posing a great threat to the world population due to its carcinogenic nature. In this study, As(III) adsorption was studied on pure and metal- (Ag- and Fe-) doped Titania nanoparticles. The nanoparticles were synthesized by liquid impregnation method with some modifications, with crystallite size in the range of 30 to 40 nm. Band gap analysis, using Kubelka-Munk function showed a shift of absorption band from UV to visible region for the metal-doped Titania. Effect of operational parameters like dose of nanoparticles, initial As(III) concentration, and pH was evaluated at 25°C. The data obtained gave a good fit with Langmuir and Freundlich isotherms and the adsorption was found to conform to pseudo-second-order kinetics. In batch studies, over 90% of arsenic removal was observed for both types of metal-doped Titania nanoparticles from a solution containing up to 2 ppm of the heavy metal. Fixed bed columns of nanoparticles, coated on glass beads, were used for As(III) removal under different operating conditions. Thomas and Yoon-Nelson models were applied to predict the breakthrough curves and to find the characteristic column parameters useful for process design. The columns were regenerated using 10% NaOH solution.